Presence of extracellular DNA in the Candida albicans biofilm matrix and its contribution to biofilms - Martins, Margarida Isabel Barros Coelho (2010)
DNA has been described as a structural component of the extracellular matrix (ECM) in bacterial biofilms. In Candida albicans, there is a scarce knowledge concerning the contribution of extracellular DNA (eDNA) to biofilm matrix and overall structure. This work examined the presence and quantified the amount of eDNA in C. albicans biofilm ECM and the effect of DNase treatment and the addition of exogenous DNA on C. albicans biofilm development as indicators of a role for eDNA in biofilm development. We were able to detect the accumulation of eDNA in biofilm ECM extracted from C. albicans biofilms formed under conditions of flow, although the quantity of eDNA detected differed according to growth conditions, in particular with regards to the medium used to grow the biofilms. Experiments with C. albicans biofilms formed statically using a microtiter plate model indicated that the addition of exogenous DNA (>160 ng/ml) increases biofilm biomass and, conversely, DNase treatment (>0.03 mg/ml) decreases biofilm biomass at later time points of biofilm development. We present evidence for the role of eDNA in C. albicans biofilm structure and formation, consistent with eDNA being a key element of the ECM in mature C. albicans biofilms and playing a predominant role in biofilm structural integrity and maintenance.